Analysis of Financial Statements as Assessing the Financial Performance (Study at the Cement Sub-Sector Manufacturing Period 2016-2018) - Suwiro Heriyanto; Ratih Purnamasari; Mega Arum; Eny Suheny; Uli Wildan Nuryanto (Ilomata International Journal of Management, 2021)
The significant growth of the domestic cement industry has increased competition between companies, thus demanding that companies improve their financial performance. For this reason, this study was conducted on three cement sub-sector companies listed on the IDX in the 2016-2018 periods with quota sampling. Researchers using comparison method to financial performance using liquidity ratios, solvency and profitability ratios with industry standard ratios. The results showed that in terms of the company's liquidity ratio of Current Ratio (CR), Quick Ratio (QR) and Cash Ratio (CsR) of PT. Indocement Tunggal Tbk and PT. Semen Baturaja Tbk shows good financial performance since above the industry average. Meanwhile, PT. Semen Indonesia Tbk shows less financial performance since the CR, QR and CsR are below the industry average. Meanwhile, in terms of the company's solvency ratio by using Debt to Equity Ratio (DER) of PT. Indocement Tunggal Tbk, PT. Semen Baturaja Tbk and PT. Semen Indonesia Tbk shows good financial performance since the DER is below the industry average, while Debt to Assets Ratio (DAR) of PT. Indocement Tunggal Tbk and PT. Semen Baturaja Tbk shows good financial performance since the DAR is below the industry average, while PT. Semen Indonesia Tbk shows less financial performance because its DAR is above the industry average. Furthermore, in terms of company profitability by using Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM) of PT. Indocement Tunggal Tbk, PT. Semen Baturaja Tbk and PT. Semen Indonesia Tbk shows less of financial performance since the ROA, ROE and NPM are below the industry average, while from Operating Profit Margin (OPM) PT. Indocement Tunggal Tbk, PT. Semen Baturaja Tbk and PT. Semen Indonesia Tbk shows good financial performance because its OPM is above the industry average.